Performance Optimization of Reconfigurable Real-Time Wireless Sensor Networks - Gasmi, Maroua (2019)
This work was supported in part by the LISI Laboratory (INSAT at University of Carthage, Tunisia), in part by the PASRI (Ministry of High Study and Research, Tunisia), in part by the Universidade Nova de Lisboa, Portugal, in part by the Complex Systems Laboratory (Jinan University, China), in part by the European Commission through MOBIDOC Grant, and in part by the Science and Technology Development Fund, MSAR, under Grant 122/2017/A3. This paper was recommended by Associate Editor D. Akopian.